Adaptive fuzzy funnel congestion control for TCP/AQM network. (December 2019) - Wang, Kun; Liu, Yang; Liu, Xiaoping; Jing, Yuanwei; Zhang, Siying
Abstract: In this paper, a performance constraint control problem is considered for Transmission Control Protocol/Active Queue Management (TCP/AQM) network with external disturbance and input saturation. On the basis of backstepping-like design procedure and fuzzy approximation technique, an adaptive fuzzy controller with prescribed constraint is achieved to ensure that the transient and steady state performances of the tracking errors can be satisfied. The stability analysis proves that all the signals in the closed-loop system are semi-globally, uniformly and ultimately bounded. The simulation results clarify the feasibility and effectiveness of the proposed approach. Highlights: A new generalized AIMD network model with input saturation and external disturbances is proposed by combining the two existing models for Transmission Control Protocol/Active Queue Management (TCP/AQM) network. A novel congestion control method is presented to solve a tracking problem by using funnel control, adaptive backstepping, and fuzzy logic systems. The steady and transient state performances of the tracking error can satisfy the design requirements.